Challenging Treatment of a Female Patient with Extensive Fournier's Gangrene - Case Report - Ognen Kostovski; Olivera Spasovska; Gjorgji Trajkovski; Svetozar Antovic; Irena Kostovska; Katerina Tosheska-Trajkovska; Biljana Kuzmanovska; Sofija Pejkova; Nikola Jankulovski (Faculty of Medicine Charles University Czech Republic, 2021)
Fournier's gangrene (FG) is a necrotizing fasciitis of the genital, perianal and perineal regions, caused by multiple anaerobic/aerobic infection. It is a rare but very serious condition with multiple long-term complications and high mortality rate. Early diagnosis and multidisciplinary approach in treatment of complicated cases of FG are crucial to the successful outcome. We report a case of an extensive FG in a 59-years-old female patient with multiple risk factors such as obesity, type 2 diabetes and hypertension. She was hospitalized as an emergency case with diabetic ketoacidosis, sepsis and extensive necrotic lesions located perineal, perianal, genital and spread to inguinal, hypogastric, gluteal and sacrococcygeal region. Fournier's gangrene was diagnosed, and after prompt resuscitation, intravenous fluids, broad-spectrum antibiotics, insulin infusion, emergency aggressive surgical debridement was performed. Several aerobic and anaerobic bacteria were isolated from wound culture and hemoculture. Patient has second debridement after four days. After second debridement was applied metabolic control, broad-spectrum antibiotics coverage, dressing the wound and negative pressure wound therapy (NPWT). Patient was discharged home five weeks after a second debridement in good condition. One month later she underwent reconstructive surgical treatment. Besides extensive FG and multiple comorbidity she was successfully managed with good outcome. Fournier's gangrene remains a life-threatening and fulminant disease which need urgent diagnosis and aggressive medical and surgical treatment, to achieve a reduction in long term complications and mortality rate.